Daclatasvir for previously untreated chronic hepatitis C genotype-1 infection: a randomised, parallel-group, double-blind, placebo-controlled, dose-finding, phase 2a trial. - Pol, Stanislas; Ghalib, Reem H; Rustgi, Vinod K; Martorell, Claudia; Everson, Greg T; Tatum, Harvey A; Hézode, Christophe; Lim, Joseph K; Bronowicki, Jean-Pierre; Abrams, Gary A; Bräu, Norbert; Morris, David W; et al. (The Lancet infectious diseases, 2012)
Several direct-acting antivirals for chronic hepatitis C virus (HCV) infection are available, but they are limited by tolerability and dosing schedules. Once-daily daclatasvir, a potent NS5A replication complex inhibitor, was generally well tolerated in phase 1 studies. We assessed daclatasvir in combination with pegylated interferon (peginterferon) and ribavirin for chronic HCV.
Keywords: Adult; Aged; Antiviral Agents; Double-Blind Method; Drug Therapy, Combination; Female; France; Genotype; Hepacivirus; Hepatitis C, Chronic; Humans; Imidazoles; Interferon-alpha; Male; Middle Aged; Placebos; Polyethylene Glycols; Recombinant Proteins; Ribavirin; RNA, Viral; Treatment Outcome; United States; Viral Load